A teoria da ação comunicativa como instrumento metodológico para compreender a educação ambiental - Viana, Rayane Rabelo Ferraz (2020)
This dissertation aimed analyze the dilemmas and challenges Critical Environmental Education, from the perspective of Communicative Action, as a possibility for social subject emancipation. The locus of research is the Maria Helena Nunes da Silva Municipal School is located in José Neves da Costa housing estate, in the municipality of Simão Dias-SE. It is a context with many social and environmental problems, among which is the contamination of the Caiçá River that passes near the school, due to the disposal of waste by the community itself, as well as the neglect by the government regarding the creation public policies to mitigate this problem. The methodological procedure used was Habermas' Theory of Communicative Action, as well as theoretical support in Paulo Freire about dialogicity. Questionnaires and interviews were applied to the educators of the school and, afterwards, a training course was conducted, analyzing the results qualitatively from the pragmatic analysis of illocutionary speech acts. Given the analysis, we affirm the enlightening force that characterizes speech acts from linguistic interactions, understanding their verbal meaning from the speaker's intentions, which enables the understanding of the type of action performed. Therefore, the formative pathway enabled an intersubjective sharing of language within a specific context that is the world of life for the understanding of political and pedagogical issues inherent in the routine of environmental educators. The synthesis of these constructions favored the creation of educational products, namely: a Study Group on Critical Environmental Education (SGCEE), a manifest letter and the elaboration of an Interdisciplinary Project on Environmental Education, which can be applied at school and replicable in other realities.